EFEKTIVITAS PENGELOLAAN ANGGARAN PADA PKBM TAMAN PENDIDIKAN DI KELURAHAN TAPA KECAMATAN SIPATANA GORONTALO - Tamsir Tamsir (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2020)
The purpose of this study was to determine and analyze the effectiveness of budget management at PKBM Education Parks in Tapa Village, Sipatana District, Gorontalo City. Based on the results of the research and discussion that has been carried out, the Budget Management at PKBM Education Park in Tapa Village, Sipatana District, Gorontalo City has been running effectively by 91.76%.